Factors Affecting the Implementation of Career Path and Mentor Method Among Hospital Based Clinical Nurses: A Study in Indonesia (International Journal of Nursing Education, 2020)
Objective. To determine the factors affecting the implementation of career path and mentor method for clinicalnurses in generalhospital, Banda Aceh-Indonesia.Method. This study used descriptive correlation with cross-sectional design,which was performed from April toJuly, 2019, on a population of 226 with 126 clinical nurses,selected using cluster sampling technique. Furthermore,the data obtained were analyzed using chi-square statistical tests and logistic regression.Result. The results identified a significant relationship between education (p = 0.017; OR = 5.489 95% Cl:1,357-22.204) and competence (p = 0.020; OR = 0.349 95% Cl: 0.144-0.846) on the implementation of career pathand mentor method. This research suggests the need for nurses to improve on the career paths chosen, by continuingeducation. Also, it is important for hospitals to facilitate scholarship budget, and organize mentor training, in order tocreate qualitative human resources (HR), which is followed by the achievement of professional services.Conclusion. The nurse’s education and competence is the path to improve the nurse’s career system. Therefore,continuing education is a breakthrough that has a positive impact and a great support for the nursing profession indeveloping its professionalism
Keywords: Factor analysis, Career path, Mentor method